PENGARUH KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Alif Hendra Prasetya; Ventje Ilat; Hendrik Gamaliel (Universitas Sam Ratulangi, 2022)
This study aims to determine the effect of dividend policy (X1), investment decisions (X2), and capital structure (X3) on firm value (Y) in banking companies listed on the Stock Exchange in 2017-2021.This research is a quantitative research by processing secondary data in the form of an annual report of a banking company. The sampling of this research was carried out using a purposive sampling method, namely the selection of samples was not random, but by using certain considerations and criteria set by researchers in the banking sector companies listed on the IDX in 2017-2021 with a total of 90 samples of observations. The data analysis method used is descriptive analysis, classical assumption testing, multiple linear regression analysis, and statistical testing. The results obtained indicate that dividend policy has a negative effect on firm value, while investment decisions and capital structure have a significant positive effect on firm value.